Information needs and information seeking behavior of quality assurance sector officers: case study in Malaysian Qualifications Agency (MQA)/ Mohd Ishak Mohd Hussaini and Raja Abdullah Yaacob - Mohd Hussaini, Mohd Ishak; Yaacob, Raja Abdullah (Faculty of Information Management, Universiti Teknologi MARA, 2012)
This study focused on the information needs, access and use quality assurance (QA) officers working in QA sector of MQA. It explored several aspects of information seeking behavior, such as information needs, reasons for seeking information, sources of information, barriers in accessing and gaining information, and access to information facilities. A total of 65 questionnaires were distributed to all officers working in QA sector of MQA. Filled-in questionnaires were returned with an overall response rate of 77 percent. The findings indicated that the most required information was current QA programs process status. Other important information needed were MQA code of practice and guidelines on good practice, and details of application. In addition, the study also revealed that all divisions shared three types of information among top ten ranking of needed information. On the other hand, problem solving and decision making were the most chosen reasons for seeking information. While, MQA databases and MQA guideline books were the main sources of information. The majorities of officers (82%) have ever faced difficulties to access and use information and unavailability of information was the main barriers reported. It was noted that 30% of officers have never visited MQA Resource Center. Meanwhile, Higher Education Institution (PD/PT) database was the most highly utilized by officers. Finally, most officers required information skill training to enhance their information seeking ability. Recommendations are made on the basis of the findings.